Synthesis and Properties of Quaternary Ammonium Gemini Surfactants with Hydroxyethyl at Head Groups. Issue 4 (18th March 2019) - Sun, Ya; Han, Fu; Zhou, Yawen; Xu, Baocai
Abstract: A series of cationic gemini surfactants Cm H2m + 1 N + (CH2 CH2 OH)2 (CH2 )s N + (CH2 CH2 OH)2 Cm H2m + 1 2Br −, referred to as m‐s‐m (OH) (m = 8, 10, 12, s = 3, 4), were prepared by quaternization of dihydroxyethyl tertiary amines with dibromoalkane. The dihydroxyethyl tertiary amines were synthesized by nucleophilic substitution of diethanolamine with bromoalkane. The characterization of the m‐s‐m (OH) surfactants was performed using 1 H NMR and MS. The surface activities and aggregation behavior in aqueous solution of the m‐s‐m (OH) surfactants were studied using surface tension measurements, dynamic light scattering (DLS), and transmission electron microscopy (TEM). The surface tension and critical micellar concentration of these surfactants in aqueous solution decreased dramatically due to the introduction of hydroxyethyl at the head group. The micelles and/or vesicles formed in the aqueous solution of m‐s‐m (OH) surfactants were strongly dependent upon the lengths of spacer chains and carbon chains. The number of vesicles increases and that of micelles decreases when the lengths of spacer chains and carbon chains increase.